2004
DOI: 10.1111/j.0030-1299.2004.13034.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential habitat use promotes sustainable coexistence between the specialist otter and the generalist mink

Abstract: 2004. Differential habitat use promotes sustainable coexistence between the specialist otter and the generalist mink. Á/ Oikos 106: 509 Á/519.Optimal foraging and habitat selection theories predict that heterogeneous environments should favour the coexistence of competitors, especially when the dominant competitor is a specialist and the sub-ordinate is a generalist. In this paper, we analysed differential habitat use as a potential mechanism for the coexistence of two competing riparian mammals, the specialis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
60
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 32 publications
7
60
0
Order By: Relevance
“…Interestingly, individuals that occupied neighbouring rivers showed different feeding habits, but during colder winters the changes in dietary habits followed similar trends for both areas: a decrease in the proportions of fish and amphibians in favour of mammals. Similar results have been reported for American mink (Maran et al 1998, Sidorovich 2000, Macdonald 2002, Bonesi and Macdonald 2004b) and other predators such as European polecat (Lode 1995, Sidorovich 2000, Macdonald 2002) and river otter (Sidorovich 2000, Macdonald 2002, Bonesi and Macdonald 2004b. The most interesting fact observed during the present study was that mink occupying neighbouring rivers showed different feeding habits, but under similar environmental conditions the niche shift between predators was almost identical.…”
supporting
confidence: 90%
“…Interestingly, individuals that occupied neighbouring rivers showed different feeding habits, but during colder winters the changes in dietary habits followed similar trends for both areas: a decrease in the proportions of fish and amphibians in favour of mammals. Similar results have been reported for American mink (Maran et al 1998, Sidorovich 2000, Macdonald 2002, Bonesi and Macdonald 2004b) and other predators such as European polecat (Lode 1995, Sidorovich 2000, Macdonald 2002) and river otter (Sidorovich 2000, Macdonald 2002, Bonesi and Macdonald 2004b. The most interesting fact observed during the present study was that mink occupying neighbouring rivers showed different feeding habits, but under similar environmental conditions the niche shift between predators was almost identical.…”
supporting
confidence: 90%
“…Erlinge (1972) identified a similar pattern comparable to our study areas, observing that despite generally favourable conditions for mink, they disappeared seasonally and locally in response to the arrival of otters. In GBRL and Salamanca, it seems that there is an interaction between otters and mink, possibly a certain degree of displacement of the American mink by the Eurasian otter when this large species temporarily occupies the suitable habitat of the first one, as has been shown previously (Dunstone 1993, Ruiz-Olmo et al 1997, Lariviè re 1999, Bonesi and Macdonald 2004a,b, Bonesi et al 2004, McDonald et al 2007). …”
supporting
confidence: 54%
“…Nevertheless, these species have to cope now with disturbed biotopes and prey populations. The re-colonising success of these species in their disturbed niches suggests a change in their foraging strategies [1,2]. However, these diet modifications are very difficult to evaluate in a low density context [3].…”
Section: Introductionmentioning
confidence: 99%